2021
DOI: 10.1016/j.omtn.2021.03.014
|View full text |Cite
|
Sign up to set email alerts
|

ncRNAs-mediated high expression of SEMA3F correlates with poor prognosis and tumor immune infiltration of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is notorious for its poor prognosis. Increasing evidence has demonstrated that semaphorin 3F (SEMA3F) plays key roles in initiation and progression of several types of human cancer. However, the specific role and mechanism of SEMA3F in HCC remains not fully determined. In this study, we first performed pan-cancer analysis for SEMA3F's expression and prognosis using The Cancer Genome Atlas (TCGA) and The Genotype-Tissue Expression (GTEx) data and found that SEMA3F might be a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 42 publications
(44 reference statements)
0
35
0
Order By: Relevance
“…Another study reported that interventional treatment of primary liver cancer can reduce serum HTATIP2/TIP30 and B7-H4 levels, improve liver function and quality of life and prolong the survival times of patients (20). A number of studies reported that SEMA3F, UCK2, NOL10, RAP2A, ZIC2 and SAC3D1 are associated with prognosis and tumour immune infiltration in hepatocellular carcinomas (21)(22)(23)(24)(25). In addition, KIF18A was reported to be associated with tumour immune cell infiltration in adrenocortical carcinomas (26).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that interventional treatment of primary liver cancer can reduce serum HTATIP2/TIP30 and B7-H4 levels, improve liver function and quality of life and prolong the survival times of patients (20). A number of studies reported that SEMA3F, UCK2, NOL10, RAP2A, ZIC2 and SAC3D1 are associated with prognosis and tumour immune infiltration in hepatocellular carcinomas (21)(22)(23)(24)(25). In addition, KIF18A was reported to be associated with tumour immune cell infiltration in adrenocortical carcinomas (26).…”
Section: Discussionmentioning
confidence: 99%
“…Upstream binding miRNAs of LOX was forecasted through the ENCORI pan-cancer analysis platform ( http://starbase.sysu.edu.cn/panCancer.php ), which consists of PITA, RNA22, miRmap, microT, miRanda, PicTar, and TargetScan programs. Only the forecasted miRNAs that simultaneously presented in five or more programs as described above were considered for following analyses ( Lou et al, 2021 ) ( Supplementary Table S1 ). The correlation between miRNAs and LOX in STAD was analyzed by the Spearman method.…”
Section: Methodsmentioning
confidence: 99%
“…The co-evolution of metastatic cancer cells with the brain microenvironment is critical for metastatic cells’ escaping dormancy and colonizing the brain. The TME landscape in brain metastases was analyzed and MG, MDMs, neutrophils, and CD8+ and CD4+ T cells have been confirmed to be the major immune cell determinants of the brain TME landscape ( 47 , 62 ). To better predict the functions of the above genes in breast cancer, we explored the correlations between gene expression level and infiltration of immune cells.…”
Section: Discussionmentioning
confidence: 99%